The 7 Rights: an active reflection tool to develop risk awareness for outdoor first aid education (International Journal of First Aid Education)
As more teachers in Nova Scotia (Canada) include the outdoors as a part of their curricular instruction, risk awareness is becoming central to their teaching practice. Central to the risk assessment for many outdoor programs is the domain of “prevent and prepare” -the first link in the Chain of Survival Behavior outlined by the International Federation of Red Cross and Red Crescent Societies (IFRC, 2016). The Certificate in Outdoor Education (COE) requires all teachers to take Advanced Wilderness and Remote First Aid (AWRFA) as a part of a college course offering in an effort to best prepare teachers to keep students safe and active outdoors. Drawing on teachers’ reflections, we present key connections made to AWRFA training, based on a debriefing tool we refer to as the “7 Rights.” The need for a focused debriefing emerged from concerns during course discussions when teachers claimed they were overwhelmed with AWRFA material, experiential first aid scenarios, and in-field care strategies. By developing a framework promoting reflective practice, the 7 Rights has potential to guide future practice by contributing to a safety culture in the effort to prevent and prepare for injuries in outdoor education.